2014
DOI: 10.2139/ssrn.2471547
|View full text |Cite
|
Sign up to set email alerts
|

Husband's Unemployment and Wife's Labor Supply The Added Worker Effect Across Europe

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
3
10
0
1
Order By: Relevance
“…This ‘reverse AWE’ in terms of employment is consistent with some previous studies of the UK which argue that the means‐tested benefit system makes work less attractive to the spouse of an unemployed partner because his benefits are reduced as her earnings increase (see McGinnity, for the UK and Bredtmann et al, for UK and Ireland combined). It may only be worth the woman working if she can earn enough to compensate for benefit reductions—so while her partner's job loss triggers an increase in search, it takes longer to find an acceptable job.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This ‘reverse AWE’ in terms of employment is consistent with some previous studies of the UK which argue that the means‐tested benefit system makes work less attractive to the spouse of an unemployed partner because his benefits are reduced as her earnings increase (see McGinnity, for the UK and Bredtmann et al, for UK and Ireland combined). It may only be worth the woman working if she can earn enough to compensate for benefit reductions—so while her partner's job loss triggers an increase in search, it takes longer to find an acceptable job.…”
Section: Resultssupporting
confidence: 87%
“…Like the US studies, Parker and Skoufias (), who compared the Mexican Peso crisis with a period of prosperity, also concluded that the AWE was stronger during a recession. Most recently, a cross‐country EU study by Bredtmann et al () found that the AWE was larger at higher levels of unemployment.…”
Section: Introductionmentioning
confidence: 99%
“…17 Moreover, we agree with the previous literature (e.g. Bredtmann et al 2014), that the AWE is hard to measure and that estimates could be confounded by unobserved partner characteristics or in our case assortative mating patterns that lead to a positive correlation of partners' shocks. We will therefore not include the regression results in section 5.…”
supporting
confidence: 86%
“…Added worker effects are expected to increase female labour supply in these circumstances. However, empirical evidence suggest that women tend to be highly limited from the demand side and are unable to materialize the job search activities (Bredtmann et al 2014). Therefore, the causes of the increase in involuntary part-time work should not merely be sought in individual precarious labour market situations of low pay or unstable employment but with the overall realization of the household work potential that enables workers to provide a decent living standard.…”
Section: Involuntary Part-time and In-work Povertymentioning
confidence: 99%